Optimization of Extraction of Compound Flavonoids from Chinese Herbal Medicines Based on Quantification Theory and Evaluation of Their Antioxidant Activity - Xu Yang; Dongli Cao; Haiyu Ji; Yingying Feng; Juan Yu; Anjun Liu (Journal of Food Quality)
Plant-derived flavonoids have been attracting increasing research interest because of their multiple health promoting effects, where numerous investigations were carried out on the optimization of extraction and bioactivities. This study aims to optimize the extraction process of compound flavonoids (CFs) from Chinese herbal medicines and detect their antioxidant activity in vitro. CFs were extracted from the raw materials named “medicine food homology,” composed of hawthorn, lotus leaf, tartary buckwheat, cassia seed, Lycium barbarum, and Poria cocos in a mass ratio of 4 :  2 :  2 :  1.5 :  1 :  1. L9 (34) orthogonal design, level effect and engineering average estimation, and quantification theory were utilized to improve the extraction method of CFs, and the predictive model for CFs yield was constructed. The 2,2ʹ-diphenyl-1-picrylhydrazyl (DPPH), 2,2ʹ-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), hydroxyl radical scavenging rate, and reducing power of CFs were measured. The highest CFs yield was obtained under the following extraction condition: liquid-solid ratio of 35 : 1 mL/g, extraction temperature of 75°C, extraction duration of 75 min, and extraction mode enzyme-assisted extraction. The forecasted yield was 37.62%. The result was accurate and the established prediction equation was reliable (R = 0.95). The antioxidant activity of CFs was significantly positively correlated with the concentration from 0.05 to 0.4 mg/mL. The DPPH, ABTS, hydroxyl radical scavenging abilities, and the reducing power of CFs were 81.82 ± 1.75%, 49.35 ± 0.09%, 89.78 ± 0.66%, and 0.232 ± 0.001 at the concentration of 0.4 mg/mL, respectively. CFs could be exploited as natural antioxidants in pharmaceuticals and functional foods.